Pengembangan Taman Rendo Menjadi Taman Bermain Anak Di Kota Ende (Dengan Pendekatan Arsitektur Hijau) - Siso, Silvester M.; lando, Maksimilianus; Mochdar, Dian Fitriawati (TEKNOSIAR, 2021)
Ende City is one of the cities in East Nusa Tenggara which has a children's playground called Taman Rendo. Rendo Park's initial function when it was built was as a recreation area with interesting photo spots. Rendo Park for the past dozen years has not been noticed so that it looks neglected and is not used by the public for recreational purposes. This is because there is no representative playground for children, so the government feels the need to develop Rendo Park into a children's playground. In the design plan, Green Architecture is the right design solution for the planned object. The method used is an architectural design method with a Green Architecture approach as a design reference. The analysis used in this design are environmental analysis, actor analysis, spatial analysis, mass shape analysis, and outdoor space analysis. Green Architecture is the right design solution for the planned object. The result is a playground that uses architectural elements as design principles to be explored. The purpose of green architecture in the design of the playground is applied to three points, namely: Building, which is a climate-responsive building concept that is in accordance with the characteristics of green architecture from mass form, roof shape, material, and structure. Landscape is an energy-efficient garden concept and the use of recycle sclupture which becomes site furniture later. Circulation is through convenience and comfort